The Effectiveness of The Demonstration Method in Enhancing Students' Speaking Skills in Retelling Folktales: A Quasi-Experimental Study in 4th grade Elementary Students - Zulfahmi, Zulfahmi; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2026)
This research is motivated by the low ability of students to convey the contents of fairy tales orally in a coherent, clear, and expressive manner. Learning is still dominated by the lecture method and does not actively involve students in speaking activities. The research method used is quantitative with a quasi-experimental approach. The data collection technique was carried out through a speaking skills test which was assessed based on indicators of fluency, mastery of content, intonation, expression, and story structure. Data were analyzed using the t-test and coefficient of determination. The results showed that the average value of students' speaking skills in the experimental class reached 90.88, while in the control class it was only 86.94. The t-test produced a T-value of 2.77> T-table 2.03 (α = 0.05), which indicates that Ho is rejected and Ha is accepted. This means that there is a significant influence of the application of the demonstration method on students' speaking skills. Furthermore, the correlation coefficient of r = 0.967 with a determination coefficient of R² = 0.935 indicates that 93.5% of the increase in students' speaking skills can be explained by the use of the demonstration method. The demonstration method has proven effective in creating an active, participatory, and enjoyable learning atmosphere. Students look more confident, enthusiastic, and able to convey stories with a logical structure and appropriate expression. The teacher acts as a model and facilitator, so that students gain direct and meaningful learning experiences. This study concludes that the demonstration method has a significant effect on improving students' speaking skills in retelling fairy tales. Therefore, this method is worthy of being used as an innovative alternative learning strategy in Indonesian language subjects in elementary schools